Comparative Study of Language Style in Adakami Advertisement and Kredit Pintar Advertisement on YouTube - Lutfi, Dea Hanursyah; Rosita, Nur (Universitas Negeri Padang, 2024)
This study aimed to compare the differences in language styles and advertising formulas used by AdaKami and Kredit Pintar advertisements on their YouTube accounts. The researcher used Joss's (1967) theory to analyze the language style. The form of research used was a qualitative comparative descriptive approach. The data for this research were obtained from advertisements by AdaKami and Kredit Pintar from January 2023 to April 2024 on their YouTube accounts. For language style, AdaKami predominantly used casual style (79.44%.), while Kredit Pintar predominantly used consultative style (58.93%). The researcher concluded that there were differences in language styles used by each brand, adapting to their target audience.